2021
DOI: 10.1039/d0ce01694b
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property correlations in piracetam polytypes

Abstract: Analysis of piracetam polytypes using energy-vector models, thermal expansion and nanoindentation measurements, produces a plausible link between their crystal structures and tableting behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…For example, we have used such models to discuss the properties of piroxicam 46 and piracetam. 47 The models comprise lines linking the centroids of molecules, scaled in length according to the magnitude of the interaction energy between the linked molecules. The most stabilizing interaction in the structure is displayed as a complete line, and less stabilizing interactions are scaled proportionally to produce gaps in the lines.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…For example, we have used such models to discuss the properties of piroxicam 46 and piracetam. 47 The models comprise lines linking the centroids of molecules, scaled in length according to the magnitude of the interaction energy between the linked molecules. The most stabilizing interaction in the structure is displayed as a complete line, and less stabilizing interactions are scaled proportionally to produce gaps in the lines.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…Namely, flexible ethyl groups in propionate anions are able to rotate, which leads to unusual lattice dynamics and phase transitions. , Regarding the layered rare-earth propionates, one could expect a highly anisotropic thermal expansion with large positive and negative linear coefficients of thermal expansion (CTEs) that could be useful for the development of high-precision thermal actuators. Indeed, many anisotropic coordination polymers are known to exhibit anomalous (anisotropic or/and negative) thermal expansion; on the other hand, there are reports on colossal negative thermal expansion (NTE) promoted by the rotation or/and reorientation of certain structural units. In particular, a combination of both factors gave rise to NTE for 1D-polymeric rare-earth pivalates where the negative α CTE of −128 MK –1 was reached . Furthermore, in general, CTEs are additionally packing-dependent. , Therefore, the studies of RE propionate polytypes and their thermal expansion represent significant interest.…”
Section: Introductionmentioning
confidence: 99%
“…52 Furthermore, in general, CTEs are additionally packing-dependent. 34,53 Therefore, the studies of RE propionate polytypes and their thermal expansion represent significant interest.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9 Moreover, Bond et al performed nanoindentation experiments and demonstrated the effect of polytypism on the mechanical properties of pharmaceutical drugs. 7,10,11…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, Bond et al performed nanoindentation experiments and demonstrated the effect of polytypism on the mechanical properties of pharmaceutical drugs. 7,10,11 Halogen-halogen interactions are moderately strong and bimodally directional, denoted as type I and type II interhalogen contacts, respectively. 12,13 These interactions aid the fabrication of the desired supramolecular structures and provide unique properties to the organic crystals, such as elasticity, plasticity, 14 and stimuli responsiveness.…”
Section: Introductionmentioning
confidence: 99%